98 Feasibility and acceptability of using a mobile phone app to assess substance use among adolescents and emerging adults. (19th September 2017) - Philyaw-Kotov, Meredith L; Rabbi, Mashfiqui; Murphy, Susan A; Klasnja, Pedrag; Tewari, Ambuj; Nahum-Shani, Inbal; Bonar, Erin E
Abstract : Substance use is an alarming public health issue, associated with morbidity, mortality, and significant societal costs. Mobile phone apps are a promising data collection and intervention delivery tool for research with substance-using youth, as most teens (73%) and young adults (92%) own a smartphone; yet, existing mobile apps in the substance use field lack data collection capabilities and require a therapist to push intervention content. Our team has developed a prototype Android mobile phone app called SARA (Substance Abuse Research Assistant), which features a customizable suite of data collection methods (e.g., sensors, ecological momentary assessments, cognitive/behavioural tasks) and allows for add-on intervention delivery components (e.g., text messages, intervention videos). To mitigate the challenges of long-term app use, SARA creates a game-like environment in which participants can earn non-financial rewards for completing assessments, such as unlocking fish to populate a virtual aquarium on the app's home screen. In May-August 2017, SARA will be field tested with 60 participants recruited from the University of Michigan Health System Emergency Department. Screened participants will be eligible if they are 14–24 years old, report past-month binge drinking (4/5 drinks tailored by gender) or recreational cannabis use, can download SARA, and provide written consent/assent. Enrolled participants will complete a baseline survey, use the app for 30 days to complete daily and weekly assessments, and provide feedback about the app at follow-up. Key findings will include: assessment compliance rates; participants' interaction with SARA during field testing; and participants' feedback about SARA, including their comfort answering sensitive questions via the app. Our findings will indicate the feasibility and acceptability of using SARA as a data collection and intervention delivery tool with substance-using youth in behavioural research.